Prevalence of reproductive tract infections and sexually transmitted infections among married women in the reproductive age group in urban slum of Bidar, Karnataka - Rathod, Dilip S.; Shelke, Ashok D.; Naik, Dhananjay B.; Kesari, Pallavi M. (International Journal Of Community Medicine And Public Health, 2017)
Background: Reproductive tract infections (RTIs) and sexually transmitted diseases (STDs) represent a major public health problem in developing countries. The consequences of RTIs are numerous and potentially devastating. The present study was conducted to give some indication of the likely burden of RTIs in urban slum of Bidar and also highlight some associated factors. Methods: This study was conducted with the objective of assessing the prevalence of various RTIs among married women in the reproductive age group of 15-44 years in an urban slum of Bidar (Karnataka) during September 2015 to February 2016. Total 357 married women in the reproductive age group of 15-44 years were interviewed. Results: The prevalence of RTI was found 36.1% with maximum prevalence of 42% in the age group of 35 years and above. Also the prevalence was high in illiterate women (53.2%), women having one or two children (54.1%), women using IUD (54.5%) and women having per capita income <Rs. 1000/- (46.35%). Conclusions: The prevalence of reproductive tract infections was most commonly associated with increasing age, illiteracy, low income, use of contraceptive methods and higher parity. The commonest reported symptom of RTI/STI was vaginal discharge. The RTI services should be focused on low income groups and health education regarding prevention and control of RTIs should be widely disseminated.